Artificial Batik Wastewater Treatment Using The Integration Method Of Electrocoagulation And Ultrasonic - Alias, Noorul Atikah (Universiti Sains Malaysia, 2021)
The textile industry consumes the most water and pollutes the water source most. Annually, hundreds of tonnes of dyes, mostly synthetic dyes, are being used worldwide which resulted in the textile effluent that generally characterized as high strength. This is due to the strong colours, high concentration of COD and BOD, high level of heavy metals and any other compounds that most likely to be toxic and harmful to the living organism. On the other hand, the batik industry in Malaysia is a part of cultural identity and most likely to exist as small and medium enterprises (SMEs). This means the effluent produced is a lot less than commercialized textile production but also means the effluent does not undergo advanced treatment before released to the water bodies. In this study to determine the dye removal percentage of artificial batik wastewater and anode material consumption, electrocoagulation is integrated with ultrasonic to enhance efficiency, mass transport rate and avoid electrode passivation. This method is executed by considering three operating parameters: inter-electrode distance, amount of voltage and treatment time using aluminium electrodes. The artificial batik sample was prepared according to the batik making process, made of ingredients such as dyes, sodium silicate, sodium carbonate, paraffin wax and tap water. Electrodes at a distance of 1cm, 2cm, 3cm are put into the beaker and connected to the DC power supply at 5V, 10, 15V, 20, 25V. The set-up was running for 25 minutes. Every 5 min interval, a 10mL sample was taken out and filtered for true and apparent colour determination and colour removal percentage. Besides, electrodes used as an anode are cleaned and weighed before and after running the treatment. Time statistical analysis of the data obtained shows the highest removal of dyes is at 2cm, 25V at 25 min with a percentage of 92.6% and 0.3254g of loss in anode weight. The colour of the batik sample went from dark purple to a subtle light blue hue.